HUBUNGAN PERSEPSI SISWA TERHADAP KETERAMPILAN PENGELOLAAN KELAS OLEH GURU DENGAN HASIL BELAJAR GEOGRAFI DI SMA NEGERI 4 PARIAMAN - ayi sagita; Khairani Khairani (JURNAL BUANA, 2021)
This study aims to determine the relationship between student perceptions of classroom management skills by teac hers and learning outcomes of geography at SMAN 4 Pariaman. This research uses quantitative research that belongs to the type of correlation research, the sample in this study consisted of 106 students of class XI IPS SMAN 4 Pariaman, the sample selection was carried out by using a positive samplig method, namely as a part or representative of the population studied as many as 63 students. data collection techniques using a questionnaire or questionnaire given to students. Based on the research results, it can be concluded that the data analysis method used is the Product Moment correlation with a level of 5% is 0.386 means that r table. This is a relationship between student perceptions of classroom management skills and student learning outcomes. The product moment coefficient of 0.386% results in a determination coefficient of 14.4%. while the remaining 85.1% is influenced by other factors that are not discussed in this study.